Manajemen Kurikulum Merdeka pada PAUD Agape: Independent Curriculum Management at Agape Early Childhood Education - Herman Suratman; Lisa G Kailola; Erni Murniarti (ITScience (Information Technology and Science), 2026)
The Independent Curriculum was developed in response to the challenges of learning during the COVID-19 pandemic and to create an education system more adaptable to current developments. Its implementation requires effective curriculum management, particularly in early childhood education (PAUD), which has unique learning characteristics. This study aims to analyze the management of the Independent Curriculum in PAUD, including its benefits, challenges, and efforts to optimize its implementation. The study used a qualitative approach with a library research method. Data were collected from various scientific sources, including journals, books, and relevant online references, and analyzed deductively and interpretively. The study results indicate that the Independent Curriculum provides flexibility in the learning process, supports the optimal development of students' potential, and enhances teachers' creativity and innovation in designing learning activities. However, its implementation still faces several obstacles, including limited facilities and infrastructure, gaps in access to technology, and teacher competency in implementing differentiated learning. Therefore, planned, systematic, and sustainable curriculum management is a key factor in overcoming these challenges. With effective management, the Independent Curriculum plays a strategic role in improving the quality of learning in PAUD through a flexible, contextual, and student-centered approach.